Cross-species microarray analysis of limb development in the bat, Miniopterus natalensis - Mason, Mandy K (Department of Biological Sciences, 2015)
This study reports the first characterisation of the embryonic bat limb transcriptome, allowing the identification of novel candidate genes that were differentially expressed between the bat hand and foot plate. These genes may have played important roles in the evolution of the bat wing and hindlimb. The reproduction and development of an African bat species, Miniopterus natalensis, was characterised and three maternal features (mass, belly size and plasma progesterone levels) examined as potential predictors of embryonic stages of development. Belly palpitation was found to be a useful field method to distinguish between non-pregnancy, early development or late development in female bats. A microarray analysis between the hand and foot plates of CS 16 and CS 17 bat embryos, and the hand plates of E 13.5 mouse embryos, revealed high correlation between the transcriptomes of the bat autopods and the mouse hand plate (r > 0.88) and among all the bat autopods (r > 0.98). However, ten genes were found to be differentially expressed in both the CS 16 and the CS 17 bat hand plate as compared to the mouse hand plate while only three genes were identified as being significantly differentially expressed between bat foot plates and mouse hand plates. A comparison between the bat hand and foot plates identified fifteen genes that were differentially expressed at the stage CS 17 stage and six at the stage CS 16. Closer examination of gene families involved in limb development revealed novel expression of genes in the retinoic acid (RA) pathway, and the Hoxd family. This included the apparent co- regulation of the 5' Hoxd genes (Hoxd10, 11, 12 and 13). Of the genes characterised in bat limb development (Hoxd13, Bmp2, Fgf8 and Prrxl), higher mRNA transcript levels in the CS 17 bat hand plate relative to the mouse hand plate was found for Hoxd13 (FC = 2.6) and Prrxl (FC = 1.8). These differences were also found in a comparison to the CS 17 bat foot plate (Hoxd13: FC = 1.4; Prrxl: FC = 1.4). A potentially novel transcript of Meis2, a gene important in specifYing the proximal-distal (P-D) axis of the limb, was noted for its high fold changes in the bat hand plate as compared the foot plate (CSI7: FC = 7.0; CSI6: FC = 2.2) and the mouse hand plate (FC = 13.1).